KULIAH TAMU: BIMBINGAN KONSELING DAN PSIKOTERAPI - Wati, Linda; Seneru, Wistina; Sutawan, Komang; Hardjasasmita, Irena Monica (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
School students may experience problems related to academic or non academic. As a candidate for Bachelor of Buddhist Religious Education Graduate who can later work as a teacher in a school, they can be faced with troubled students who need help in order to study well. Counseling techniques are interventions that can be given to school students who have these problems. Guest lecture was given to 5th semester students studying in the Counseling and Psychotherapy course in Sekolah Tinggi Ilmu Agama Buddha (STIAB) Jinarakkhita Lampung on December 6, 2022. The activity was carried out online via Zoom application at 1-3.30 pm where 33 students and 2 lecturers were present. The presentation of the material given to students focuses on application, important aspects, and practical experience of the presenter regarding the use of counseling and psychotherapy. Students fill out the pretest form before the presentation was given and students fill out the posttest form after the material presentation and question answer were carried out. The pretest and posttest form were filled in using Google Form. Based on the evaluation results from pretest and posttest, it seems that the students are able to differentiate between counseling and psychotherapy techniques, understand the important things needed to do counseling, and the attitudes that need to be trained in order to become good counselors.